Prevalence of clinically silent corticotroph macroadenomas. (27th July 2016) - Guttenberg, Katie B.; Mayson, Sarah E.; Sawan, Carla; Kharlip, Julia; Lee, John Y.; Martinez‐Lage, Maria; Loevner, Laurie A.; Ewanichak, Jayme; Grady, M. Sean; Snyder, Peter J.
Summary: Objective: The prevalence of clinically silent corticotroph macroadenomas is unknown. Our aim was to determine the prevalence of clinically silent corticotroph macroadenomas among all pituitary macroadenomas. Design: Patients scheduled to have transsphenoidal surgery for any sellar mass were prospectively evaluated clinically and biochemically. Patients: Adults who were scheduled for transsphenoidal surgery for a sellar mass at a single academic medical centre. Measurements: Patients were assessed clinically prior to surgery and graded as having typical, mild or no Cushingoid features. They were assessed biochemically by plasma ACTH and 24‐h urine free cortisol (UFC). Excised tissue was examined histologically, and pituitary macroadenomas, examined by immunohistochemistry. Patients with corticotroph macroadenomas were classified as clinically silent if they exhibited no Cushingoid features but had elevated plasma ACTH and/or 24‐h UFC. They were classified as totally silent if they exhibited neither Cushingoid features nor elevated plasma ACTH or 24‐h UFC. Results: Of 124 patients who had pathologically confirmed pituitary macroadenomas, 20 (16%) had corticotroph macroadenomas. Eight (40%) of these were clinically silent, in that they had no Cushingoid features but could be identified biochemically by elevated plasma ACTH (seven) and/or 24‐h UFC (three). Five (25%) were totally silent. Conclusions: A substantial minority (16%) of pituitary macroadenomas treated surgically are corticotroph adenomas. Of these, 40% are clinically silent but can be recognized by elevated plasma ACTH and/or 24‐h UFC. Recognizing these adenomas may influence the surgical approach and provide a marker by which to follow the response to treatment.